2014
DOI: 10.3923/bj.2015.13.24
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Fluorescent Pseudomonas spp. from Diverse Agro-Ecosystems of India and Characterization of their PGPR Traits

Abstract: Plant growth promoting rhizobacteria are known to rapidly colonize the rhizosphere and suppress soil borne pathogens at the root surface. Among the Gram-negative soil bacteria, Pseudomonas is the most abundant genus in the rhizosphere and the PGPR activity of some of these strains has been known for many years. From diverse agro-ecosystems of India, 75 strain of fluorescent Pseudomonas spp. were isolated and all of them were tested for various PGPR traits like phytohormones production, HCN, EPS, siderophores a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Among the four functional clusters analyzed in this paper (pseudomonads, spore-forming bacteria, actinobacteria, and mesophilic bacteria), pseudomonads were the group with the highest capacity, being all the selected isolates able to produce NH 4 + and NO 2 − /NO 3 − , and this result confirmed some literature reports. For example, Kumar et al [22] studied 75 isolates of Pseudomonas and found that all were NH 4 + producers, although at different levels (weak, moderate, or high). Moreover, Bacillus isolates showed a high degree of ammonium production (75%) and nitrification (60%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the four functional clusters analyzed in this paper (pseudomonads, spore-forming bacteria, actinobacteria, and mesophilic bacteria), pseudomonads were the group with the highest capacity, being all the selected isolates able to produce NH 4 + and NO 2 − /NO 3 − , and this result confirmed some literature reports. For example, Kumar et al [22] studied 75 isolates of Pseudomonas and found that all were NH 4 + producers, although at different levels (weak, moderate, or high). Moreover, Bacillus isolates showed a high degree of ammonium production (75%) and nitrification (60%).…”
Section: Discussionmentioning
confidence: 99%
“…The experiment was done as reported previously [22]. Bacteria were inoculated in test tubes containing Peptone Water medium [23].…”
Section: Methodsmentioning
confidence: 99%
“…Ammonia production by bacterial cultures was assayed in a peptone water medium (Peptone 1%, NaCl 0.5%), and incubated for 48 h at 37 • C in a shaker incubator. Ammonium accumulation was tested by adding 0.1 mL Nessler's reagent and observed for the development of yellow-brown color [24].…”
Section: In Vitro Analysis Of Plant Growth-promoting Traitsmentioning
confidence: 99%
“…Some of the isolates exhibited a strong ammonia producing ability. HCN production have been reported to play an essential role in the biological control of pathogenic fungi and deleterious rhizobacteria (Kumar et al, 2015). The possible use of siderophores as biopesticides paved special interest to study Pseudomonas (Wilson, 1997).…”
Section: Discussionmentioning
confidence: 99%